1995
DOI: 10.1063/1.358776
|View full text |Cite
|
Sign up to set email alerts
|

Al and B ion-implantations in 6H- and 3C-SiC

Abstract: Low (keV) and high (MeV) energy Al and B implants were performed into n-type 6H- and 3C-SiC at both room temperature and 850 °C. The material was annealed at 1100, 1200, or 1400 °C for 10 min and characterized by secondary ion mass spectrometry, Rutherford backscattering (RBS), photoluminescence, Hall and capacitance-voltage measurement techniques. For both Al and B implants, the implant species was gettered at 0.7 Rp (where Rp is the projected range) in samples implanted at 850 °C and annealed at 1400 °C. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…[2][3][4] Ion implantation at elevated temperatures ͑hot implantation͒ is known to reduce damage and enhance the activation of impurities, but it also introduces extended defects such as dislocation loops, which degrade the electrical properties. 3,5,6 For compound semiconductors, ion beam induced epitaxial crystallization ͑IBIC͒ often produces better crystal quality than thermal annealing, but for SiC, the mechanism of IBIC is complex and still under investigation. 7 Therefore, the study of the annealing behavior of defects in ion-implanted SiC is important for fabricating SiC devices.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Ion implantation at elevated temperatures ͑hot implantation͒ is known to reduce damage and enhance the activation of impurities, but it also introduces extended defects such as dislocation loops, which degrade the electrical properties. 3,5,6 For compound semiconductors, ion beam induced epitaxial crystallization ͑IBIC͒ often produces better crystal quality than thermal annealing, but for SiC, the mechanism of IBIC is complex and still under investigation. 7 Therefore, the study of the annealing behavior of defects in ion-implanted SiC is important for fabricating SiC devices.…”
Section: Introductionmentioning
confidence: 99%
“…The only difference observed between the two spectra are the weak sharp lines at 2.623 eV, 2.588 eV, and 2.586 eV in the implanted sample. These lines are associated with defects induced by the ion implantation [9]. The relatively small intensity of these lines and the similarity between both spectra, suggested that the annealing treatment has recovered the crystalline quality of the substrate.…”
Section: Resultsmentioning
confidence: 87%
“…Lattice damage that occurs in SiC during implantation can be minimized by performing ion implantation at a high temperature, around 800°C. [15][16][17] While aluminum implants in SiC have been found to be stable during annealing, [18][19][20] substantial dopant re-distribution of boron 10 and gallium 21 has been observed during annealing leading to dopant loss or gettering at the SiC surface as a result of Si evaporation from the lattice. Additionally, degradation of the surface leads to an increase in the number of surface traps and an unwanted decrease in carrier mobility in surface channel regions.…”
Section: Introductionmentioning
confidence: 97%